ANALISIS ASUHAN KEPERAWATAN MELALUI INTERVENSI FISIOTERAPI DADA (CLAPPING) PADA BAYI DENGAN DIAGNOSIS MEDIS BRONKOPNEUMONIA DI RSUD PASAR REBO - nur salmawati; Rizqi Nursasmita (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2023)
Abstrack Background: During the growth period, especially infants, toddlers, and children where their organs have not functioned optimally which results in them being more susceptible to various diseases, one of which is respiratory tract disease, namely bronchopneumonia. Inflammation that occurs in bronchopneumonia causes increased secretion production to the point of causing existing clinical manifestations that cause problems and one of these problems is ineffective airway clearance. The impact that can occur if airway clearance is ineffective, is not treated immediately, which can cause hypoxia. This can occur due to a lack of oxygen supply due to accumulation of secretions and if the oxygen supply is not met it can cause the patient to lose consciousness, seizures, permanent brain damage, stop breathing and even death. One of the nursing actions that can be performed on infants with ineffective airway clearance is chest physiotherapy (clapping). In this case, clapping is one of the techniques from a series of chest physiotherapy that can be performed on patients with bronchopneumonia with the aim of helping remove secretions and improve respiratory efficiency and help clear the airway. Objective: To analyze nursing care through chest physiotherapy intervention (clapping) with ineffective airway clearance problems with a diagnosis of bronchopneumonia. Method: this study consisted of conducting chest physiotherapy nursing interventions (clapping) for 3 days in two infants with ineffective airway clearance nursing problems in the Rose Room of Pasar Rebo Hospital. Result: The results of the nursing evaluation on the main nursing problem of ineffective airway clearance based on progress notes after chest physiotherapy intervention (clapping) on ​​By. R and By. A for 3 days with a frequency of 1 time per day, data were obtained on the third day of nursing action, namely that both clients experienced decreased sputum production and no crackles were found in both lungs. On By. R breathing frequency 52 times per minute to 44 times per minute, whereas in By. A respiratory rate of 50 breaths per minute becomes 42 breaths per minute. Conclusion: giving chest physiotherapy intervention (clapping) can overcome the problem of ineffective airway clearance nursing as evidenced by decreased sputum production and no crackles in both baby's lungs. Keywords: chest physiotherapy, clapping, ineffective airway clearance.